A Case of Immediate Hypersensitivity Reaction to Maltitol - Ana Rodríguez Trabado; Carmen Cámara Hijón; José Antonio García-Trujillo; Irene Magriz Trascón; Luis Miguel Fernández Pereira (Case Reports in Medicine)
Background. Maltitol is a sugar alcohol that is frequently used as a noncaloric sweetener, although it is also used as an excipient, a plasticizer in gelatin capsules, and an emollient. It has not been previously described as an agent involved in immediate hypersensitivity reactions. Methods. We report on an anaphylactoid reaction with pharyngeal occlusion suffered by a 60-year-old man after ingestion of a candy containing maltitol syrup. A prick-to-prick test was performed with the candy and maltitol powder. Other allergens were excluded as causative agents of the adverse reaction, although the patient refused to undergo an oral challenge test with the candy. A basophil activation test (BAT) was performed with maltitol powder, and a dose-response curve was generated. The test was also performed in 3 healthy controls. Results. Both prick-to-prick tests were negative. The result of the BAT was positive at all the concentrations tested in the patient’s blood and negative in all the controls. Conclusions. The BAT can help to clarify the agents implicated in an adverse reaction and can reduce the risk involved in diagnosis. The BAT can also prove useful in the study of reactions caused by low-molecular-weight antigens, for which routine diagnostic tests are not feasible.